A survey of perspectives on safety, health, and emergency preparedness among employees: A case study at Bentong Community College - Khairiana, Razali; Mohammad Adam, Adman; Nurul Fairuz, Buang (AL-HAJJAJ Enterprise, 2023)
Every organisation must prioritise safety, health and emergency preparedness. Negligence and a lack of emergency awareness are the leading causes of accidents. This study examines how Bentong Community College employees perceive safety, health, and emergency preparedness. This study was conducted at one community college in Bentong district, located on the East Coast of Peninsular Malaysia. A standardised questionnaire that was given to 43 employees of Bentong Community College who responded to an online survey served as the study's instrument. Descriptive statistics are used to analyse the data. Results revealed that most Bentong Community College employees believed safety, health, and emergency preparedness were crucial. Additionally, the outcome demonstrated that employees know the significance of safety, health, and emergency preparation. Bentong Community College could be an excellent example of prioritising safety, health, and emergency preparedness for other Community Colleges in different states of Malaysia.